Scientometric Analysis of the Global Scientific Literature on Circularity Indicators in the Construction and Built Environment Sector - Gomis K; Kahandawa R; Jayasinghe RS (MDPI (Basel, Switzerland), 2022)
The circular-economy-related research has exponentially increased in recent years. The literature shows that circularity indicators represent a timely topic that requires an in-depth analysis. However, the trends and gaps in the literature in the area of the circular economy have not need analysed in depth. This study uses a scientometric analysis as the research methodology to examine the current literature on circularity and circular economic indicators. The publications were extracted from the Web of Science and were published until the end of the third quarter of 2022. The scientometric analysis was conducted using VOSviewer software to map the relationships between the 1117 articles selected on the topic. The findings revealed that the most productive author and university were Jorge de Brito and Delft University of Technology in the Netherlands. The overlay visualisation of the keywords identified a notable shift in research themes from dynamics, frameworks, models, and design in previous years to economy, barriers, and strategies in the current research context. The overlay visualisation of the keywords identified trending research hotspots within the current research context. This study is the first holistic and global overview of circularity and circular economic indicators in the construction context and identifies a critical need for further research to understand circularity and circular economic indicators under co-occurrence analysis conditions. This study offers academics, policymakers, and other circularity activists a guide for future research and valuable insight into circularity and circularity indicator themes.
Keywords: circularity indicators; circular economy; scientometric analysis; sustainable cities and communities; sustainable consumption and production; built environment; VOSviewer